PARAMETRIC STUDY OF NATURAL CONVECTIVE AND RADIATIVE HEAT TRANSFER IN INCLINED CYLINDRICAL ANNULI - Hadi Al-Hafidh, Manal; S. Safwat, Lina (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
The unsteady state laminar mixed convection and radiation through inclinedcylindrical annulus is investigated numerically. The two heat transfer mechanisms ofconvection and radiation are treated independently and simultaneously. The outercylinder was kept at a constant temperature while the inner cylinder was heated withconstant heat flux. The study involved numerical solution of the governing equationswhich are continuity, momentum and energy equations using finite difference method(FDM), where the body fitted coordinate system (BFC) was used to generate the gridmesh for computational plane. A computer program (Fortran 90) was built to calculatethe bulk Nusselt number (Nub) after reaching steady state condition for fluid Prandtlnumber fixed at (Pr =0.7) (for air) with radius ratio ( =1.5, 2.6, 5.0), Rayleigh number(0≤Ra≤103),Reynolds number (50≤Re≤2000), dimensionless heat generation (0≤Q≤10),Conduction-Radiation parameter (0≤N≤10), optical thickness (0 ≤ t≤ 10) and differentannulus inclination with horizontal plane (0°≤δ≤90°). For the range of parametersconsidered, results show that radiation enhance heat transfer. It is also indicated in theresults that Nu increase with the increasing of inclination angle δ, Ra, Re, and Q. Thecorrelation equations are concluded to describe the radiation effect.Comparison of the result with the previous work shows a good agreement.